Oncolytic Viruses for Cancer Immunotherapy - Ahmed, Ashraqat (Libyan International Medical University Faculty of AMS, 2022)
In preclinical and clinical research, oncolytic virotherapy has yielded promise but limited results. Induction of tumor-specific immunity is an important therapeutic mechanism of oncolytic virotherapy, in addition to direct oncolytic activity. As a result, the insertion of immune stimulator genes and sensible combinatorial therapy with other immunotherapies can boost the efficacy of oncolytic viruses.
Oncolytic Viruses for Cancer Immunotherapy